The role of vaginal maturation value assessment in prediction of vaginal pH, serum FSH and E2 levels - (:unkn) unknown (My University, 2006)
Introduction: The objective of this study is to detect the correlation between vaginal maturation value (MV) and vaginal pH measurement, serum FSH and E2 levels in women without vaginal infection. Materials And Methods: Fifty women with vasomotor symptoms were enrolled at the present study. All women underwent vaginal pH assessment, measurement of serum FSH and E 2 levels and vaginal MV measurement in addition to routine follow-up. For determination of vaginal MV, pap smear from lateral vaginal wall was obtained and evaluated. Results: In women with atrophic symptoms, the age and vaginal pH levels were significantly higher than women without these symptoms. Highly significant correlation between vaginal pH, vaginal MV and serum FSH was detected. Similarly highly significant inverse correlation was present between vaginal pH levels and vaginal MV. Discussion: In summary, this study confirms that vaginal pH and MV are similar to FSH in the identification of patients who have low estrogen levels or who are menopausal. Methods of deriving vaginal pH and MV are simple, practical, quick and economic. As a conclusion, the present study demonstrated that vaginal pH measurement and vaginal MV assessment is similar in diagnosis and monitoring of estrogen deficiency in women with urogenital atrophic symptoms.
Keywords: Menopause; pH; Vaginal maturation value